Acquisition of Skilled Reading in Costa Rican Students Through Pictophonic Strategies - Carpio-Brenes, María de los Ángeles (2017)
The following article describes the results of a study carried out in Costa Rica in 2011 with the objective of confirming the acquisition of reading expertise in second grade students who were taught to read with Pictophonic Strategies for two years, in comparison with other students who used the Eclectic Method during the same period of time. Reading expertise is understood as the use of two necessary procedures to decode words: the lexical route for the acknowledgment of known words, and the sub-lexical route for unknown words. An experimental pre-post design study was carried out with a control group, using the letter recognition test of the LEE Test at the beginning of the 2010 school year; and, at the end of the 2011 school year, the phonetic segmentation, word and pseudo-word reading tests were implemented. The significant differences between both methods point towards Pictophonic Strategies as a proposal that develops experienced reading.